Pengaruh Penggunaan Asam Folat terhadap Kadar Hemoglobin Pasien Penyakit Ginjal Kronik yang Menjalani Hemodialisis Di RSUD Abdul Wahab Sjahranie (Journal of Tropical Pharmacy and Chemistry, 2016)
Chronic kidney disease is a pathophysiological process with diverse etiology, resulting in a progressive decrease in renal function, and generally end up kidney failure.1 The aim of this research was to determine the effect of use folic acid on hemoglobin levels in patients with chronic kidney disease with hemodialysis in the hospital Abdul Wahab Sjahranie Samarinda. The research design used in this study are pre-experimental form one group pretest-posttest design. Subjects consisted of 30 people who fit in inclusion criteria. The analysis includes univariate analysis by finding frequency distribution and bivariate analysis with paired t test. The result showed that there is a difference between hemoglobin levels before and after hemodialysis (pValue 0,001).